Poly[[di-μ-aqua-(μ-4-formyl-2-methoxyphenolato)disodium] 4-formyl-2-methoxyphenolate] - Asghar, Muhammad Nadeem (International Union of Crystallography, 2010)
In the title coordination polymer, {[Na(2)(C(8)H(7)O(3))(H(2)O)(4)](C(8)H(7)O(3))}(n), all the non-H atoms except the water O atoms lie on a crystallographic mirror plane. One sodium cation is bonded to four water O atoms and one vanillinate O atom in a distorted square-based pyramidal arrangement; the other Na(+) ion is six-coordinated by four water O atoms and two vanillinate O atoms in an irregular geometry. One of the vanillinate anions is directly bonded to two sodium ions, whilst the other only interacts with the polymeric network by way of hydrogen bonds. In the crystal, a two-dimensional polymeric array is formed; this is reinforced by O—H⋯O hydrogen bonds, which generate R (2) (1)(6) and R (2) (2)(20) loops.